2023
DOI: 10.4142/jvs.22168
|View full text |Cite
|
Sign up to set email alerts
|

In vitro embryo production from ewes at different physiological stages

Abstract: Background The collection of ovaries from slaughterhouses is an important source of oocytes for in vitro embryo production. On the other hand, the physiological stage of slaughtered females varies and influences embryo production. Objectives The study examined the in vitro efficiency of embryos and demi-embryos from young, non-pregnant adult, and pregnant adult ewes from a local slaughterhouse. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 37 publications
(56 reference statements)
0
1
0
Order By: Relevance
“…Hernández et al [47] reported a low number of nuclei (44.2 ± 9.9) present in parthenogenetic blastocysts of O. aries and in interspecies cloned blastocysts of O. aries and Ovis canadensis mexicana (46.7 ± 8.1 nuclei). Lorenzo-Torres et al [48] reported 122 nuclei in good-quality blastocysts produced by IVF. These results are lower than those obtained in the present study, but they are similar to those reported by Agata et al [49], Mastrorocco et al [50], and Nadri et al [51].…”
Section: Effect Of Resveratrol On Embryo Qualitymentioning
confidence: 99%
“…Hernández et al [47] reported a low number of nuclei (44.2 ± 9.9) present in parthenogenetic blastocysts of O. aries and in interspecies cloned blastocysts of O. aries and Ovis canadensis mexicana (46.7 ± 8.1 nuclei). Lorenzo-Torres et al [48] reported 122 nuclei in good-quality blastocysts produced by IVF. These results are lower than those obtained in the present study, but they are similar to those reported by Agata et al [49], Mastrorocco et al [50], and Nadri et al [51].…”
Section: Effect Of Resveratrol On Embryo Qualitymentioning
confidence: 99%